The pinch-off dynamics of bubbles coated by microparticles - Wang,H; Brito-Parada,PR (Journal of Colloid and Interface Science, 2020)
HypothesisWhile the pinch-off dynamics of bubbles is known to be influenced by changes in surface tension, previous studies have only assessed changes due to liquid properties or surfactant effects at the air-liquid interface but not due to the presence of particles. The current study proposes that particles at the air-liquid interface play an important role in changing the surface tension and thus the pinch-off dynamics of particle-laden bubbles.ExperimentsHigh-speed photography was used to study the pinch-off dynamics of air bubbles coated by a monolayer of silica microparticles. The influence of bubble surface coverage and particle size classes on the bubble pinch-off dynamics were explored.FindingsWe identify that although the scaling exponent of the power law that governs the pinch-off of coated and uncoated bubbles is the same, the pinch-off dynamics is distinctly different when particles are present at the air-liquid interface due to a decrease in surface tension with time in the neck region. We suggest that the surface pressure generated by particle interaction reduces the pinch-off speed by reducing the apparent surface tension. We observe that the apparent surface tension is dependent on particle size but not on the percentage of bubble surface coated by particles.